Floating remote-controlled water sampling device - Brunclík, Tomáš (University of Pardubice, 2021)
A floating water sampling device suitable for taking samples for remote sensing algorithm development or operational monitoring of multiple water bodies has been developed. The device is based on remote-controlled boat and the attached Van-Dorn sampler. Such a setup belongs to the category of unmanned surface vehicles being convenient for taking near-surface water samples off-shore from a distant site. Its efficiency compared to traditional sampling with an inflatable boat has been proved by reducing the average time between the consecutive samplings to about a half.
Keywords: water quality; sampling; remote control; unmanned surface vehicle